1980
DOI: 10.1111/j.1365-2222.1980.tb02137.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cell‐mediated immunity and suppressor T‐cell function in asthmatic and normal children

Abstract: Summary The role of general and suppressor T‐cell function was investigated in a group of twelve children with atopic asthma and ten non‐atopic control children. Studies of active E rosettes, lymphocyte stimulation, and delayed type skin responsiveness revealed no statistically significant group differences. Data obtained employing a concanavalin A‐induced, suppressor T‐cell assay revealed that the asthmatics generated significantly less suppressor cell activity than did the normal control group. There was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Oral theophylline has been shown to result in an increase in CD8 + cells in peripheral blood samples (28–30). However, another paediatric study found a reduction in suppressor T‐cells similar to that observed in our group of patients with no difference whether or not the children were treated with theophylline (31). This is in accordance with our results.…”
Section: Immunomodulatory Effectssupporting
confidence: 86%
“…Oral theophylline has been shown to result in an increase in CD8 + cells in peripheral blood samples (28–30). However, another paediatric study found a reduction in suppressor T‐cells similar to that observed in our group of patients with no difference whether or not the children were treated with theophylline (31). This is in accordance with our results.…”
Section: Immunomodulatory Effectssupporting
confidence: 86%
“…The number of T lymphocytes, T suppressor subset and their functional activity in asthmatic patients have been examined but results remain controversial. Some authors have reported normal T-lymphocyte numbers and activity in asthmatic patients (McGeady, Saraclar & Mansmann, 1976;Harper et al, 1980), while others reported depressed T-cell numbers and function (Gupta et al, 1975;Grove et al, 1975). Data concerning the subpopulations of T lymphocytes in children with bronchial asthma and the effect of theophylline treatment on this subpopulation have been published by Gupta, Fikrig and Good (1980) and Harper et al (1980).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported normal T-lymphocyte numbers and activity in asthmatic patients (McGeady, Saraclar & Mansmann, 1976;Harper et al, 1980), while others reported depressed T-cell numbers and function (Gupta et al, 1975;Grove et al, 1975). Data concerning the subpopulations of T lymphocytes in children with bronchial asthma and the effect of theophylline treatment on this subpopulation have been published by Gupta, Fikrig and Good (1980) and Harper et al (1980). In the present study eleven children with extrinsic asthma were studied before and 1 month following theophylline treatment testing both the T-cell activity as well as the T-suppressor-cell subset.…”
Section: Introductionmentioning
confidence: 99%
“…A relative defi-ciency of suppressor T lymphocytes has been reported in patients with allergic rhinitis (11,12), atopic dermatitis (13), and both allergic (14) and nonallergic asthma (15,16). A decrease in T lymphocyte suppressor cell numbers and in mitogen induced suppressor cell activity has been described in asthma (17)(18)(19)(20)(21)(22). A decrease in peripheral blood suppressor cells has been shown in chronic asthmatics who were refractory to corticosteroid therapy (23).…”
Section: Introductionmentioning
confidence: 99%